2012
DOI: 10.1038/ng.2405
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genomic analysis identifies SOX2 as a frequently amplified gene in small-cell lung cancer

Abstract: Small-cell lung cancer (SCLC) is an exceptionally aggressive disease with poor prognosis. Here, we obtained exome, transcriptome and copy-number alteration data from approximately 53 samples consisting of 36 primary human SCLC and normal tissue pairs and 17 matched SCLC and lymphoblastoid cell lines. We also obtained data for 4 primary tumors and 23 SCLC cell lines. We identified 22 significantly mutated genes in SCLC, including genes encoding kinases, G protein–coupled receptors and chromatin-modifying protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
865
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 930 publications
(940 citation statements)
references
References 46 publications
43
865
1
2
Order By: Relevance
“…More recently, whole-genome sequencing of SCLC specimens have uncovered potential driver mutations such as PTEN mutation or FGFR1 amplification, both of which occur at relatively low frequency (28,30). In one previous study, SOX2 amplification was found in approximately 27% of SCLC samples, and SOX2 knockdown by shRNA inhibited proliferation of SCLC cells with SOX2 gene amplification (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, whole-genome sequencing of SCLC specimens have uncovered potential driver mutations such as PTEN mutation or FGFR1 amplification, both of which occur at relatively low frequency (28,30). In one previous study, SOX2 amplification was found in approximately 27% of SCLC samples, and SOX2 knockdown by shRNA inhibited proliferation of SCLC cells with SOX2 gene amplification (30).…”
Section: Discussionmentioning
confidence: 99%
“…2B). SOX2, another transcription factor previously implicated in lung cancer (28), is also highly expressed in DMS53 cells, but was only modestly affected at the highest concentration of JQ1 tested (Fig. 2B).…”
Section: Jq1 Regulates Ascl1 Expression In Sclcmentioning
confidence: 98%
“…13). Three landmark studies comprehensively characterized the SCLC genomic landscape, identifying alterations in genes encoding histone modifying proteins and transcription factors, including SOX2 and NOTCH family genes (10,14,15). These studies revealed a mutation rate of 5.5 to 8.6 coding mutations per Mb (10,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…85 Interestingly, SOX2 amplification was found in 27% of samples. SOX proteins are involved in stem cell renewal, as are the NOTCH and Hedgehog pathways, which were also frequently dysregulated.…”
Section: Issues In Specific Tumor Typesmentioning
confidence: 99%